How Important is it to Score a Goal? The Influence of the Scoreline on Match Performance in Elite Soccer. Issue 3 (December 2014) - Lago-Peñas, Carlos; Gómez-López, Maite
The goal of this study was to examine the effects of three different scorelines (1 Goal Up, Level Score, 1 Goal Down) on match performance indicators in elite soccer. Ball possession decreased when teams were 1 goal up. High Range Budget Clubs (HRBC) and Upper-Mid Range Budget Clubs (UMRBC) dominated possession against their opponents whether winning, losing, or drawing. Lower-Mid Range Budget Clubs (LMRBC) and Low Range Budget Clubs (LRBC) had less possession than HRBC. The probability of reaching the final one-third of the pitch decreased when teams were 1 goal up. LMRBC and LRBC had less match final third entries than HRBC. Similarly, shots on goal decreased when teams were 1 goal up. These findings could be used by coaches and match analysts when they evaluate performance and develop training drills.